P1_4 Global Warming: Effects on LEO Satellites - Michelbach, Christian; Holmes, Luke; Treacher, Dan (Physics Special Topics, 2014)
Satellites in low Earth orbits are subject to drag forces from the Earth’s atmosphere, these forces deorbit the satellites over time. The effect of global warming on the rate at which a satellite will deorbit is investigated in this paper. It is found that, while a simplified model would predict a faster deorbit, this is not the case due to interactions at the molecular level.